Investigation of Johne's disease in Tasmanian fallow deer (Dama dama). Issue 1 (15th October 2020) - Jackson, RB; Kennedy, DJ; Sergeant, ESG
Abstract : In 2012 when many sheep flocks in northern‐central Tasmania were experiencing a high prevalence of ovine Johne's disease, 34 wild adult fallow deer shot on or near infected properties were negative to microscopic Mptb lesions of the ileo‐caecal valve, terminal ileum and ileo‐caecal lymph nodes. This study demonstrated 95% confidence of detecting Johne's disease in this fallow deer population if ≥10% of animals were shedding Mycobacterium avium subsp. paratuberculosis in their faeces, or if ≥21% of animals were sub‐clinically infected.